2004
DOI: 10.1111/j.0908-8857.2004.03217.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial phylogeny of Locustella and related genera

Abstract: Red'kin, Y. A. and Rohwer, S. 2004. Mitochondrial phylogeny of Locustella and related genera. */ J. Avian Biol. 35: 105 Á/110.We used maximum likelihood analysis of complete mitochondrial ND2 sequences (1041 bp) to clarify the taxonomy and relationships of various species and genera of grass and bush warblers. The tree revealed two clades of grass and bush warblers. One clade was comprised of all four western Palearctic Locustella and two species of Asian Bradypterus. The other clade included five eastern Pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 16 publications
1
59
0
Order By: Relevance
“…"]; Stepanyan, 1990). Both Drovetski et al (2004) and Alström et al (2011a) showed that these two are markedly different genetically, supporting treatment as separate species. Alström et al (2011a) Alström et al (2011a) and an earlier study by Drovetski et al (2004), found slight divergences between L. pleskei and L. ochotensis, and noted that their status as separate species needs to be studied further.…”
Section: Locustellidaementioning
confidence: 82%
See 1 more Smart Citation
“…"]; Stepanyan, 1990). Both Drovetski et al (2004) and Alström et al (2011a) showed that these two are markedly different genetically, supporting treatment as separate species. Alström et al (2011a) Alström et al (2011a) and an earlier study by Drovetski et al (2004), found slight divergences between L. pleskei and L. ochotensis, and noted that their status as separate species needs to be studied further.…”
Section: Locustellidaementioning
confidence: 82%
“…All of the genera with more than one representative were found to be non-monophyletic: Bradypterus was separated into an Asian and an African clade, with Locustella and Megalurus pryeri nested within the former, and the monotypic Malagasy Dromaeocercus within the latter; only two of the five Megalurus species formed a clade that did not include other genera, and both Cincloramphus and Eremiornis were nested in one of the Megalurus clades. The non-monophyly of Bradypterus and Locustella had previously been found based on mitochondrial ND2 sequences of all Locustella, two Asian and three African Bradypterus and two Megalurus (M. pryeri and M. gramineus) (Drovetski et al, 2004). Moreover, the affinity of M. pryeri to Locustella had previously been suggested based on morphology (Morioka and Shigeta, 1993).…”
Section: Locustellidaementioning
confidence: 90%
“…Our laboratory procedures and PCR profile for ND2 amplification followed Drovetski et al (2004). For both samples the mtDNA ND2 gene was amplified using GoTaq Ò (Promega, Wisconsin, USA) PCR reagents with primers L52 15-TATCGGGCCCATACCCCGAAAAT (Hackett 1996) and H1064 CTTTGAAGGCCTTCGGTTTA (Drovetski et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…For both samples the mtDNA ND2 gene was amplified using GoTaq Ò (Promega, Wisconsin, USA) PCR reagents with primers L52 15-TATCGGGCCCATACCCCGAAAAT (Hackett 1996) and H1064 CTTTGAAGGCCTTCGGTTTA (Drovetski et al 2004). The fragments were sequenced on ABI 3730 using amplification primers and an internal primer L347 CCATTC CACTTCTGATTCCC (Drovetski et al 2004). …”
Section: Methodsmentioning
confidence: 99%
“…Total genomic DNA was extracted using the DNeasy Blood and Tissue Kit (QIAGEN, Valencia, CA, USA). We used GoTaq Green Master Mix (Promega, Madison, WI, USA) and primers L5215: 5¢-TATCGGGCCCATACCCCG AAAAT-3¢ (Hackett, 1996) and H1064: 5¢-CTTTGAAGGCCTTCGGTTTA-3¢ (Drovetski et al, 2004) for fragment amplification via PCR. The PCR profile included 2.5 min preheating at 94 1C and 35 cycles of 30 s at 94 1C, 30 s at 57 1C and 45 s at 72 1C.…”
Section: Methodsmentioning
confidence: 99%